64-jährige Patientin mit pulmonalen Rundherden - Gompelmann, Daniela; Heußel, Claus Peter; Schnabel, Philipp Albert; Herth, Felix (Deutsche medizinische Wochenschrift, 2010)
Thieme E-Books & E-Journals